Multicenter validation of a score to predict prognosis after the development of HCC recurrence following liver transplantation. Issue 6 (June 2019) - Goldaracena, Nicolás; Mehta, Neil; Scalera, Irene; Sposito, Carlo; Atenafu, Eshetu G.; Yao, Francis Y.; Muiesan, Paolo; Mazzaferro, Vincenzo; Sapisochin, Gonzalo
Abstract: Background: HCC recurrence after LT impacts negatively on survival. A recent study detected late recurrence (≥12 months), alpha-fetoprotein (AFP) <100 ng/mL at recurrence and being amenable for curative-intent treatments as good prognostic factors. With these variables a prognostic score was proposed. The objective of this study was to validate the prognostic score for hepatocellular carcinoma (HCC) recurrence following liver transplantation (LT). Methods: Data from the University of California, San Francisco, the University Hospital of Birmingham and Instituto Nazionale dei Tumori, Milan including patients with HCC recurrence after LT were analyzed. The previous reported score was applied to this cohort. Results: From June 2002–December 2014, 1328 patients had a confirmed HCC in their explanted liver. The study group comprised 130 patients (9.8%) diagnosed with HCC recurrence after LT. Overall median survival after HCC recurrence was 12.4 (95% CI 10.2–16.3) months. Application of the previously reported score showed a significantly superior survival for the good prognosis group compared to moderate and poor prognosis groups (p < 0.0001). Conclusion: The score continues to identify a group of patients who would benefit from aggressive treatment and experience significant improved survival following recurrent HCC after LT.